CHALLENGES AND OPPORTUNITIES OF BLIND MASSEURS IN INCREASING COMPETENCY THROUGH IMPLEMENTATION BUSINESS STANDARDS OF MASSAGE PARLOR - Gayatri, Ida Ayu Made; Suriata, I Nengah (ADI Publisher, 2020)
The purpose of this study was to analyze the challenges and opportunities of Indonesian blind masseurs in improving competency through the implementation of the business standards of massage parlor. The research method is a descriptive-qualitative, theoretical approach on competency in human resource management. Primary data sources selected by purposive sampling. The informants involved were representatives of blind massage entrepreneurs. Secondary data sources in this study is PERMENPAR No.20 of 2015 concerning Business Standards of Massage Parlor. Data analysis techniques by means of data triangulation. The results of the study indicate the challenges faced by the blind masseurs namely: 1) requirements of massage business licenses have not been fulfilled; 2) aspects of the organization, management, and human resources have not been maximized. Increasing the competency of the masseur as a traditional health practitioner is an innovation, and it can extend their opportunities to work in the center of public health and hospitals. Keywords: competency, standards, blind, masseur